Understanding the diagnostic process of Bipolar Disorder: A qualitative study of bipolar patients in Cape Town, South Africa - Battiston-Weggelaar, Claire (Department of Psychology, 2017)
Bipolar Disorder (BD) is a complex psychiatric disorder posing many diagnostic challenges. Recent international research has highlighted a concerning rise in the number of patients diagnosed worldwide with BD each year. Although many studies have been conducted over the past two decades that aimed to assist in reducing misdiagnosis rates of BD, few have focussed on this topic from the perspective of those suffering with the disorder. Furthermore, no African or South African research could be found on this topic, which supports the need to investigate this phenomenon more in-depth from a South African perspective. The aim of this study was to deepen the current understanding of the diagnostic process of BD in a sample of South African patients. This was achieved by exploring the diagnostic journeys of 12 participants diagnosed with BD through semi-structured, qualitative interviews. A grounded theory of diagnostic patterns and the factors that might mitigate and complicate this process was then formed. The results highlight the unique and often contradictory experiences of each participant, which calls into question the attempt to simplify the diagnostic process of BD. In this sample of 12 BD patients, no two diagnostic experiences were the same. Factors that were found to influence this process include: (1) the DMI pattern (Depression-Mania-Interval) where a manic episode naturally follows a depressive episode, which occurs first and is often diagnosed and treated as unipolar depression; (2) the ever-broadening definition and revised DSM-5 diagnostic criteria for BD, culminating in the highly controversial concept of a bipolar spectrum; (3) the diagnostic interview and the need for clinicians to carefully consider all differentials, as well as the patient's ability or willingness to convey important information, before making a diagnosis; (4) the role of primary care physicians (GPs), who are often the first port of call for patients seeking help for their symptoms; (4) the collection of collateral information from people close to the patient and the opaque consequences thereof; (5) implicit expectations of patients from treating clinicians and how this informs help-seeking behaviour. Although common trends in diagnostic processes could be identified that echo what existing literature has already found, there were just as many unique outcomes, ambiguities and contradictions evident in these results. Thus, future research would do well to focus on this instead to obtain new and unique insights that could assist in better understanding, diagnosing and treating BD in generations to come.